2008
DOI: 10.1523/jneurosci.5333-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Consolidation to aradishand Protein Synthesis-Dependent Long-Term Memory after Single-Session Appetitive Olfactory Conditioning inDrosophila

Abstract: In Drosophila, formation of aversive olfactory long-term memory (LTM) requires multiple training sessions pairing odor and electric shock punishment with rest intervals. In contrast, here we show that a single 2 min training session pairing odor with a more ethologically relevant sugar reinforcement forms long-term appetitive memory that lasts for days. Appetitive LTM has some mechanistic similarity to aversive LTM in that it can be disrupted by cycloheximide, the dCreb2-b transcriptional repressor, and the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
370
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(402 citation statements)
references
References 70 publications
(156 reference statements)
30
370
1
1
Order By: Relevance
“…Amnesiac is a putative neuropeptide whose release probably would be impacted by shi ts1 on a slower time scale. Indeed there is some evidence that longer-duration blocking of shi ts1 in DPM neurons can ablate performance fully (39,40), an effect that, by definition, includes both ASM and ARM.…”
Section: Resultsmentioning
confidence: 99%
“…Amnesiac is a putative neuropeptide whose release probably would be impacted by shi ts1 on a slower time scale. Indeed there is some evidence that longer-duration blocking of shi ts1 in DPM neurons can ablate performance fully (39,40), an effect that, by definition, includes both ASM and ARM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, crammer mutant flies were reported to either show 12 or not show 13 an appetitive short term memory deficit with identical memory retention scores, because the scores of the control “CS” flies were different in the two studies. Our results further emphasize the need for a more systematic scheme addressing control populations.…”
Section: Discussionmentioning
confidence: 99%
“…The water maze is a learning paradigm characterized by a motivation to escape from water, whereas the MAZE test used in the current study is a learning paradigm characterized by motivation to receive a reward. It has been reported that appetitive long-term memory (LTM) is consolidated more quickly than aversive LTM [36,37]. Moreover, Hirano et al showed that different LTM systems are utilized in the hungry state [38].…”
Section: Discussionmentioning
confidence: 99%